Severe Orthostatic Hypotension Complicating Multiple Myeloma. Issue 3 (November 2017) - Sury, Krishna; Mutter, Marina; Moeckel, Gilbert W; Perazella, Mark A
Introduction: Amyloidosis is a well-recognized complication of multiple myeloma, although isolated vascular amyloidosis of the kidney is relatively rare. Vascular amyloidosis is associated with fewer urinary findings than the more common glomerular amyloidosis, and may present both diagnostic and treatment challenges, particularly when performing renal replacement therapy. Case description: We present a 53-year-old man who presented with light-headedness complicated by multiple falls, severe orthostatic hypotension, and acute kidney injury. The patient was ultimately diagnosed with multiple myeloma. His course was complicated by progressively worsening kidney function, which necessitated renal replacement therapy, and persistent symptoms of orthostatic hypotension despite maximal medical therapy. A kidney biopsy revealed light chain cast nephropathy and isolated vascular amyloidosis of the kidney. Hemodialysis and subsequently continuous veno-venous hemodialysis were poorly tolerated due to severe hemodynamic instability. Ultimately, the patient suffered a fatal cardiac arrest. Conclusions: This case provides a platform to discuss clinical aspects and diagnosis of vascular-limited renal amyloidosis. In addition, we address the difficulty in managing a patient with severe hemodynamic instability due to this disease.